F-KiCo (Fetal-Kick Count) Innovation Needs Analysis for Monitoring Fetal Well-Being and Maternal-Fetal Attachment - Purwati, Yuni - (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Fetal movement is an indicator of fetal well-being that can be monitored independently by pregnant women. Counting fetal movements affects the attention and maternal-fetal attachment which has an impact on health practices and the health of the baby. The problem is that pregnant women don't care about the importance of counting fetal movements and in practice counting they often forget or fall asleep before getting ten counts. Objective: to analyze the experiences and needs of independent fetal well-being monitoring devices by pregnant women that can stimulate maternal-fetal attachment. Methods: In-depth interviews were conducted on ten primigravidas at 24-36 weeks' gestation, the instrument was a researcher using an interview guide. Data analysis uses data compaction techniques, data presentation and conclusion/verification. Result: based on coding analysis of keywords, ten categories and four themes were found, namely the perception of the benefits of counting fetal movements; previous experience and behavior; obstacles to the implementation of fetal motion counts; expectations about the method/tool for calculating fetal motion. Conclusion: the findings of the theme underlie the need for the development of a fetal kick count that can be used in monitoring fetal well-being independently by pregnant women and stimulating maternal-fetal attachment.